(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
The word inclusive refers to a positive thing: an effort to unite children with disabilities by providing practical and comprehensive teaching methods (Sukadari, 2019). One thing which is important in implementing inclusive education is the readiness of the teachers by improving their competencies to adapt with inclusive students. Therefore, this research is aimed to explore the ability of prospective teachers in facing the era of inclusive-based education.The scope of this research is limited to analyze the linguistics ability, in this case the ability to comprehend basic-sign language, and the spirit of inclusive education in UIN Sultan Maulana Hasanuddin Banten. This research is based on the thoughts that prospective teachers need to be equipped with sign language that will be useful for them when they are teaching in inclusive schools. The results showed that the sign language skills of prospective teachers were still very limited. However, after learning sign language, their ability increases by 100%.In other words, prospective teachers are ready to adapt when they teach in inclusive schools later. Keywords: Basic-Sign Language, Inclusive Education, Inclusive School